Pistachio Shell-derived Activated Carbon as an Efficient Bio-adsorbent for River Water Treatment - Pradhananga Adhikari, Mandira; Nepal, Bishal; Suwal, Dhurba; Manandhar, Sarita; Shahi, Sabina; Yadav, Amar Prasad; Adhikari, Nanda Bikram (Journal of Institute of Science and Technology, 2025)
The remediation of river water using activated carbon is one of the economic solutions to overcome the water shortage problem. Nanoporous-activated carbons (ACs) were synthesized from pistachio shell powder using phosphoric acid as the activating agent. Various impregnation ratios of pistachio shell powder to phosphoric acid were used to activate the precursor and then carbonized at 400℃ for three hours in a nitrogen atmosphere. The activated carbons (ACs) were characterized using Scanning Electron Microscopy (SEM), Raman scattering, and Fourier Transform Infrared Spectroscopy (FTIR), semi-quantitative surface information was determined using Boehm titration, and iodine and methylene blue adsorption. The iodine adsorption was maximum (758.45 mg/g) at an impregnation ratio of 1:1.5 (precursor: phosphoric acid, PSC_1.5). Boehm titration and FTIR spectra showed oxygenated functional groups such as hydroxyl, carboxyl, and carbonyl are present in the pistachio shell-derived activated carbon (PSC_1.5). Langmuir and Freundlich models are best fitted for methylene blue adsorption. The coefficient of the determinant was comparatively higher for the Langmuir model than the Freundlich model with an adsorption capacity of 243 mg/g. The efficiency of PSC_1.5 for the treatment of Bagmati river water was studied. The physical and chemical properties reveal that the river water is excessively polluted and changes to clean and clear water after the treatment with PSC_1.5. It removed more than 80% of contaminants from the river water, and significantly improved water quality to the WHO limits. Therefore, it is considered that activated carbon from pistachio shells is useful as an efficient bio-adsorbent for the treatment of Bagmati River water.